Study of the influence of ascorbyl palmitate and amiodarone in the stability of unilamellar liposomes - Benedini, Luciano Alejandro (2014)
Amiodarone (AMI) is a low water-solubility drug, which is very useful in the treatment of severe cardiac disease. Its adverse effects are associated with toxicity in different tissues. Several antioxidants have been shown to reduce, and prevent AMI toxicity. The aim of this work was to develop and characterize Dimyristoylphosphatidylcholine (DMPC) liposomal carriers doped with ascorbyl palmitate (Asc16) as antioxidant, in order to either minimize or avoid the adverse effects produced by AMI. The employment of liposomes would avoid the use of cosolvents in AMI formulations, and Asc16 could minimize the adverse effects of AMI. To evaluate the partition and integration of AMI and Asc16 in lipid membranes, penetration studies into DMPC monolayers were carried out. The disturbance of the liposomes membranes was studied by generalized polarization (GP). The stability of liposomes was evaluated experimentally and by means of the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. The size particle and zeta potential (z) values of the liposomes were used for application in calculations for attractive and repulsive forces in DLVO theory. In experimental conditions all of these vesicles showed stability at time 0, but only DMPC + Asc16 10% + AMI 10% liposomes kept their size stable and z during 28 days. These results are encouraging and suggest that such systems could be suitable for AMI delivery formulations.